Days of Hope - Magazieva, Zulay (Germany, 2011)
This film tells the story of six of the 5,000 plus people who have "disappeared” in Chechnya since the beginning of the second Chechen War in 1999. Working in an adverse environment, Zulay Magazieva has interviewed relatives of the disappeared, filmed when mass graves were being dug up, and brought her footage out of the country in order to finish her film. Although it took her ten years to finally make this film, the actuality of the problem unfortunately remains unchanged. The film intends to explain the universal reality of “disappearances” and draw attention to the limits of international justice.
Verzio Film Festival Submission
Duration: 00:29:00
Verzio Film Festival Submission
Keywords: Documentary films